An Extension of the Procedural Deficit Hypothesis from Developmental Language Disorders to Mathematical Disability - Evans, Tanya M.; Ullman, Michael T. (Frontiers in Psychology, 2016)
Math disability (MD) is a neurodevelopmental disorder affecting mathematical abilities. Here we propose a new explanatory account of MD, the Procedural Deficit Hypothesis (PDH), that may further our understanding of the disorder. According to the PDH of MD, abnormalities of brain structures underlying the procedural memory system can lead to difficulties with math skills learned in this system, as well as problems with other functions that depend on these brain structures. This brain-based account is motivated in part by the high comorbidity between MD and language disorders such as dyslexia that may be partly explained by the PDH, as well as by the likelihood that learning automatized math skills should depend on procedural memory. Here we first lay out the PDH of MD, and then present specific predictions, examining the existing literature for each while pointing out weaknesses and gaps to be addressed by future research. Although we do not claim that the PDH is likely to fully explain MD, we do suggest that the hypothesis could have substantial explanatory power, and that it provides a useful theoretical framework that may advance our understanding of the disorder.